2019
DOI: 10.1177/2292550319876663
|View full text |Cite
|
Sign up to set email alerts
|

A 3-Year Review of an Outpatient Burn Sedation Program in a Tertiary Burn Care Centre: Is It Safe and Does It Work?

Abstract: Introduction: The burn treatment room at our tertiary-care centre is run by a multidisciplinary team, providing care to primarily burn patients who require moderate to deep sedation to undergo dressing changes in a monitored setting outside the operating room. There is little literature on the safety, efficacy, and logistics of treating outpatient pediatric burn patients in this manner. This study reviews the safety of deep sedation in the burn treatment room. Methods: A retrospective chart review of patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…The data of patients with second-degree burn treated in our hospital from February 2019 to February 2020 were retrospectively analyzed, and the patients were enrolled according to the following inclusion and exclusion criteria. Inclusion criteria: (1) the patients were diagnosed with second-degree burn after examination [ 11 ]; (2) the patients received treatment within 24 hours after injury and were treated in our hospital in the whole course without transferring to other hospitals during treatment or stopping treatment; (3) the patients did not present obvious shock; (4) the burn depth was relatively uniform, and the wound surface was red and white by observation; and (5) the patients were over 18 years old.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The data of patients with second-degree burn treated in our hospital from February 2019 to February 2020 were retrospectively analyzed, and the patients were enrolled according to the following inclusion and exclusion criteria. Inclusion criteria: (1) the patients were diagnosed with second-degree burn after examination [ 11 ]; (2) the patients received treatment within 24 hours after injury and were treated in our hospital in the whole course without transferring to other hospitals during treatment or stopping treatment; (3) the patients did not present obvious shock; (4) the burn depth was relatively uniform, and the wound surface was red and white by observation; and (5) the patients were over 18 years old.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, scholars Gravelier et al also proved that Shaoshang Shengji ointment was able to effectively treat small area burns, cause less obvious scars, and present significant efficacy [ 9 ]. Previous studies have shown that application of Shengji ointment in patients with second-degree burns might be beneficial to improve their wound healing rate, but practice has indicated that the wound pain caused by burns can seriously affect the treatment willingness of patients, and some patients suffer from intolerable pain when changing fresh dressing, leading to poor treatment compliance [ 10 , 11 ]. To improve the effect of topical drugs, some scholars suggested treating burn patients with immersion therapy and found that such therapy can easily remove the outer dressings, alleviate the pain from dressing changing, and completely clean the wound surface, which can effectively prevent infections.…”
Section: Introductionmentioning
confidence: 99%